Humoral Antibodies in Patients After Renal Homotransplantation - Iwasaki, Yoji (1967)
Humoral antibodies have been demonstrated by antiglobulin consumption tests to be present in the serum of virtually all patients after renal homotransplantation. The most completely characterized was a γG immunoglobulin distinct from the Forssman antibody which reacts against sheep but not against human red cell antigens, and which absorbs selectively against panels of human liver, kidney or white blood cells. This antibody appeared within a few days or weeks after transplantation, usually shortly after a rejection episode, and was more or less continuously detectable thereafter. The antibody was found in all of 10 patients studied during the first 4 post-transplant months, and in 13 of 14 patients tested from 4 months to more than 2 years after operation. Preliminary observations are included on another humoral antibody which does not react with sheep RBC stromata, but which can also be measured with a modified antiglobulin consumption test. The latter antibody was less commonly demonstrable, but it also exhibited specific absorption characteristics when tested against a panel of leukocytes obtained from volunteers. The implications of these findings are discussed in relation to the possible value of such sera for histocompatibility typing, as well as the possible role of such antibodies in promoting homograft enhancement.